2006
DOI: 10.1007/s10482-006-9067-9
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Bacillus strains as potential probiotics and subsequent confirmation of the in vivo effectiveness of Bacillus subtilis MA139 in pigs

Abstract: A total of 124 samples were collected from the intestine of broiler chickens, piglet faeces, fermented foods, soils and Chinese herbs. More than 750 strains of aerobic, spore-forming bacteria were isolated from these samples. The inhibitory activity of these spore-forming strains against Escherichia coli K88, E. coli K99, Salmonella typhimurium and Staphylococcus aureus was assessed using a disc plate diffusion assay. The six bacilli with the largest inhibition zones against the four indicator bacteria were ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
109
1
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 161 publications
(126 citation statements)
references
References 32 publications
7
109
1
7
Order By: Relevance
“…The genus Bacillus is widely diversified and spread throughout the world from many sources such as air, soil, water, and gastrointestinal tracts of animals and humans (Guo et al, 2006, Earl et al, 2007, Rintala et al, 2008. Many species are extremophyles, or tolerant to more strict conditions such as high alkalinity, acidity, salinity or temperature (Niehaus et al, 1999, Horikoshi, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…The genus Bacillus is widely diversified and spread throughout the world from many sources such as air, soil, water, and gastrointestinal tracts of animals and humans (Guo et al, 2006, Earl et al, 2007, Rintala et al, 2008. Many species are extremophyles, or tolerant to more strict conditions such as high alkalinity, acidity, salinity or temperature (Niehaus et al, 1999, Horikoshi, 2008.…”
Section: Introductionmentioning
confidence: 99%
“…Os probióticos são definidos como aditivos alimentares de microrganismos vivos os quais os benefícios afetam o animal hospedeiro melhorando o equilíbrio da microbiota intestinal (FULLER et al,1989). Segundo Vanbelle et al (1990), após uma dosagem oral efetiva, são capazes de estabelecer-se no trato gastrintestinal e manter ou aumentar a microbiota natural, ajudando a prevenir a colonização por microrganismos patogênicos, assegurando melhor utilização dos nutrientes (HOLZAPFEL et al, 2001;SCHAREK et al, 2005;GUO et al, 2006). Há inúmeros trabalhos verificando a utilização de probióticos em bezerros, pois as primeiras semanas de vida são muito importantes para seu desenvolvimento e produção futuros.…”
Section: Introductionunclassified
“…25 Several studies have showed that Bacillus spores can be found in the intestinal tracts of animals where they live and multiply actively, raising the question of whether this could be where they live and grow. [25][26][27][28][29][30] For instance, has been reported that soil carries approximately 10 6 spores/g of soil while human feces present an average of up to 10 4 spores/g. The numbers of spores found in human feces, is too high to be accounted for principally by ingestion of food contaminated with spores from soil.…”
mentioning
confidence: 99%
“…is commensal bacteria of the GI-track. 26,27,31,32 Other major advantages of spores over vegetative (LAB) cells are their thermostability to high temperatures spores can survive at 235°F (113°C) for 8minutes. 28,33,34 This thermostability property allow incorporate the spores into the feed the during the milling and pelletizing of the feed and other applications as production of vaccines incorporate as adjuvants.…”
mentioning
confidence: 99%
See 1 more Smart Citation